Giant parathyroid adenoma diagnosed by brown tumor, a clinical manifestation of primary hyperparathyroidism: a case report - Banu Yigit; Mert Tanal; Bulent Citgez (Journal of the Pakistan Medical Association, 2021)
Brown tumor (BT) is the pathological expression of osteitis fibrosa cystica owing to primary and secondary hyperparathyroidism (HPT). It is a rare benign lesion of skeletal system that usually affects the facial bones, clavicles, ribs, pelvis and extremities. The purpose of this case report is to present the clinical, pathological and radiological findings of BT, rarely seen in adults, originating from the giant parathyroid adenoma and emerging as the first clinical sign of HPT. The patient underwent a successful parathyroidectomy operation and on the first postoperative day, the patient was discharged without any complications. Continuous...